CRIMINAL LIABILITY FOR RESISTANCE TO A REPRESENTATIVE OF AUTHORITY OR A PERSON PERFORMING A CIVIL DUTY - Begaliyev, Mirjalol (KLINIK VA FUNDAMENTAL TIBBIYOT TADQIQOTLARI JURNALI, 2026)
This article is devoted to the topic of “Criminal liability for resisting a representative of the authorities or a person performing his civil duty” and, based on Article 219 of the Criminal Code of the Republic of Uzbekistan, examines the structure of this crime, its objective and subjective signs, qualification issues and judicial practice. The article includes a legal analysis of the crime, a comparative analysis with foreign experience (the Russian Federation, the Republic of Kazakhstan and the countries of the European Union) and directions for improvement. The article consists of an introduction, two main parts and a conclusion and is intended for undergraduate students. The purpose of the research is a legal analysis of the structure of this crime and an assessment of the possibilities for improving the legislation. As a result, legal proposals are given. The article is based on the Criminal Code, judicial practice and international experience.